Pengaruh Profitabilitas, Struktur Modal, dan Komisaris Independen Terhadap Kualitas Laba Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia - Meyra Putri Faradina; Fera Damayanti; Syarbini Ikhsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of profitability, capital structure, and independent commissioners on earnings quality in banking sector companies listed on the Indonesia Stock Exchange for the 2021–2023 period. Profit is an important part of financial statements because it reflects the company's ability to generate stable profits in each period. Earnings quality is the main indicator in assessing the reliability of a company's financial information. This study uses a quantitative method with secondary data obtained from the annual reports of each company. Data analysis was carried out using IBM SPSS version 26 through descriptive statistical tests, classical assumption tests, multiple linear regression, and hypothesis tests. The study population was banking companies listed on the IDX for the 2021–2023 period, with a purposive sampling technique that resulted in 30 companies and a total of 90 observations. The results of the study show that simultaneously, profitability, capital structure, and independent commissioners have a positive effect on earnings quality. Partially, profitability and capital structure have a significant positive effect, while independent commissioners have no effect on earnings quality.